2011
DOI: 10.1111/j.1365-294x.2010.04994.x
|View full text |Cite
|
Sign up to set email alerts
|

Who are the missing parents? Grandparentage analysis identifies multiple sources of gene flow into a wild population

Abstract: In order to increase the size of declining salmonid populations, supplementation programmes intentionally release fish raised in hatcheries into the wild. Because hatchery-born fish often have lower fitness than wild-born fish, estimating rates of gene flow from hatcheries into wild populations is essential for predicting the fitness cost to wild populations. Steelhead trout (Oncorhynchus mykiss) have both freshwater resident and anadromous (ocean-going) life history forms, known as rainbow trout and steelhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 46 publications
(67 reference statements)
3
107
1
Order By: Relevance
“…Offspring from the above-waterfall resident population described earlier also produced significant numbers of smolts and returning anadromous adults despite over 70 years of complete selection against migration (see also Hayes et al 2012;. Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013).…”
Section: Oregon; Sloat and Reeves 2014mentioning
confidence: 99%
See 4 more Smart Citations
“…Offspring from the above-waterfall resident population described earlier also produced significant numbers of smolts and returning anadromous adults despite over 70 years of complete selection against migration (see also Hayes et al 2012;. Likewise, freshwater maturation persists in many, if not all, hatchery steelhead trout stocks after decades of selectively breeding only anadromous adults (Christie et al 2011;Sharpe et al 2007;Sloat and Reeves 2014). Otolith microchemistry revealed that anadromous kelts in the Yakima River basin, Washington, had resident mothers 7% and 20% of the time in each of 2 years of study (Courter et al 2013).…”
Section: Oregon; Sloat and Reeves 2014mentioning
confidence: 99%
“…Larger individuals attempt to dominate access to females through aggressive competition, whereas smaller individuals rely more on sneaking tactics to surreptitiously fertilize eggs during spawning (Fleming 1996). The size differences of males using alternative mating tactics can be great (Fleming and Reynolds 2004), though small sneaking males can still have significant reproductive success (Christie et al 2011;Martinez et al 2000;Morán et al 1996;Seamons et al 2004). Males therefore more frequently become residents because they are less dependent on large body size for reproductive success than females, and as a result, they mature across a much greater range of ages and sizes (Jonsson and Jonsson 1993;Roni and Quinn 1995).…”
Section: Fitness Trade-offs In Partially Migratory Salmoninesmentioning
confidence: 99%
See 3 more Smart Citations